Low interest rates and executive risk-taking incentives: Evidence from the United States - Paula Castro; Maria T. Tascon; Francisco J. Casta\~no; Borja Amor-Tapia (BRQ Business Research Quarterly, 2021)
This article contributes to the literature by indicating how certain monetary policies impact the compensation incentives of US managers to adopt riskier business policies. Specifically, based on the agency problems between shareholders and managers and between shareholders and creditors, a research framework is developed to identify the influence of low interest rates on managers' risk-taking incentives proxied by the sensitivity of executive compensation to stock return volatility (Vega). We examine 1,293 firms in the United States between 2000 and 2016, and the results indicate that low interest rates increase the managers' short-term risk-taking incentives and that those incentives contribute to the risk effectively taken by the firm. Our results are robust to the use of alternative monetary proxies and to the presence of passive versus active institutional shareholders.
Keywords: E41; E43; E51; M12; M52; 650; Executive compensation; monetary policies; low interest rates; managers' risk-taking incentives; ZLB policy